Exploring Stroke Therapy in Non-Urban Area: A Qualitative Descriptive Study - Kartika Setia Purdani; Somporn Rungreangkulkij (GLOBAL HEALTH SCIENCE GROUP, 2024)
Someone who survives a stroke attack with live change is called a stroke survivor. Several limitations both of physics and psycho as an impact from stroke attack need attention, with no expectation in a non-urban area. The most common intervention for it is complementary therapy, which combines conventional medicine and non-conventional treatments. Sociodemographics, beliefs, values, and culture are considered for use. This study aims to explore stroke therapy in non-urban areas—methods: A qualitative descriptive study supported by 17 participants. Participants’ observations and in-depth interviews are collecting data methods. Content analysis is used to analyze data for this research. The setting area for this research is Samarinda, East Kalimantan, Indonesia. The study results are three themes that represent the participants interviewed. These were 1)preventing joint stiffness and muscle weakness, 2)cooking, and 3)seeking spiritual support. Stroke disease has the golden period for acute care and rehabilitation training times; when optimizing this time, the loss of body function is controlled. Long-term care for stroke survivors needs several supports, including complementary therapy. Instruction, instructor, and right, safe guidance are necessary for continued recovery in a community setting.